Slow and stored light via electromagnetically induced transparency using a Λ-type superconducting artificial atom - Kai-I Chu; Xiao-Cheng Lu; Kuan-Hsun Chiang; Yen-Hsiang Lin; Chii-Dong Chen; Ite A. Yu; Wen-Te Liao; Yung-Fu Chen (Physical Review Research)
Recent progresses in Josephson-junction-based superconducting circuits have propelled quantum information processing forward. However, the lack of a metastable state in most superconducting artificial atoms hinders the development of photonic quantum memory in this platform. Here we use a single superconducting qubit-resonator system to realize a desired Λ-type artificial atom, and to demonstrate slow light with a group velocity of 3.6 km/s and the microwave storage with a memory time extending to several hundred nanoseconds via electromagnetically induced transparency. Our results highlight the potential of achieving microwave quantum memory, promising substantial advancements in quantum information processing within superconducting circuits.